To come to a better understanding : medicine men and clergy meetings on the Rosebud Reservation, 1973-1978 - Garner, Sandra L., 1954- (University of Nebraska Press, 2016)
"To Come to a Better Understanding examines the intercultural (mis)understandings between medicine men and Jesuit priests during a five-year dialogue on the Rosebud Indian Reservation from 1973-1978"--Provided by publisher